The effect of alphacypermethrin-treated mesh protection against African horse sickness virus vectors on jet stall microclimate, clinical variables and faecal glucocorticoid metabolites of horses - Patrick Page (BMC Veterinary Research, 2017)
Abstract Background African horse sickness (AHS) is of importance to health and international trade in horses worldwide. During export from and transit through AHS endemic countries or zones, physical and chemical measures to protect horses from the vectors of AHS virus (AHSV) are recommended by the World Organization for Animal Health. Protection of containerized air transport systems for horses (jet stalls) with alphacypermethrin insecticide-treated high density polyethylene mesh is effective in reducing the Culicoides midge vector attack rate. In order to determine the effect of this mesh on jet stall ventilation and horse welfare under temperate climatic conditions, jet stall microclimate, clinical variables and faecal glucocorticoid metabolite (FGM) levels of 12 horses were monitored during overnight housing in either a treated or untreated stall in two blocks of a 2 × 3 randomized crossover design. Results Temperature difference between the treated stall and outside was significantly higher than the difference between the untreated stall and outside at 1/15 time points only (P = 0.045, r = 0.70). Relative humidity (RH) difference between the treated stall and outside did not differ from the untreated stall and outside. Temperature and RH in the treated stall were highly and significantly correlated with outside temperature (r = 0.96, P < 0.001) and RH (r = 0.95, P < 0.001), respectively. No significant differences were detected between rectal temperatures, pulse and respiratory rates of horses in the treated stall compared to the untreated stall. Mean FGM concentrations for horses housed in the treated stall peaked earlier (24 h) and at a higher concentration than horses housed in the untreated stall (48 h), but were not significantly different from baseline. No significant difference was detected in FGM concentrations when the treated and untreated stall groups were compared at individual time points up to 72 h after exiting the jet stall. Conclusions Alphacypermethrin-treated HDPE mesh could be used under temperate climatic conditions to protect horses in jet stalls against AHSV vectors, without compromising jet stall microclimate and horse welfare.